Tunay na repormang agraryo ipaglaban (AV014, 1988)
Features the three-day Agrarian Reform Express staged by the Kilusang Magbubukid ng Pilipinas (KMP). Affiliate peasant group from Northern Luzon and Southern Luzon traveled hundreds of kilometers to reach Manila